Weather forecast for simulation models of agroecosystem production - Žiniauskaitė, Eugenija; Denisovas, Vitalijus (Lietuvos matematikos rinkinys, 1998)
The forecast of the agroecosystem fate including the rate of crop development and expected yield are considered as the basic tasks of the dynamic agroecological modelling system that has been developed at the University of Klaipėda.This paper describes the development and adaptation in Lithuania of the stochastic weather simulator. Once the parameters of the simulator are identified it allows the user to simulate the weather conditions of the current vegetation period, and therefore, to use the whole modelling system for calculations of various prognostic scenario.The dynamics of main daily weather elements such as min and max daily temperatures, relative air humidity, cloudiness, precipitation and wind speed are described by discrete time stochastic processes. The first four elements are considered as the four-dimensional discrete time process while two others are modelled separately. Parameter identification as well as weather generation procedures are described and the verification of the stochastic weather simulator is carried out using the data from Lithuanian state hydrometeorological network.